2021
DOI: 10.1021/acsnano.1c02103
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology for Boosting Cancer Immunotherapy and Remodeling Tumor Microenvironment: The Horizons in Cancer Treatment

Abstract: Immunotherapy that harnesses the human immune system to fight cancer has received widespread attention and become a mainstream strategy for cancer treatment. Cancer immunotherapy not only eliminates primary tumors but also treats metastasis and recurrence, representing a major advantage over traditional cancer treatments. Recently with the development of nanotechnology, there exists much work applying nanomaterials to cancer immunotherapy on the basis of their excellent physiochemical properties, such as effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(86 citation statements)
references
References 282 publications
0
86
0
Order By: Relevance
“…However, some studies showed that particles with a size in the range of 100–150 nm with a positive charge enter tumor cells more easily. 30–32 Fig. 1 shows the properties of nanoparticle drug delivery systems that determine their activity.…”
Section: Essential Properties Of Paclitaxel Nanomedicinementioning
confidence: 99%
“…However, some studies showed that particles with a size in the range of 100–150 nm with a positive charge enter tumor cells more easily. 30–32 Fig. 1 shows the properties of nanoparticle drug delivery systems that determine their activity.…”
Section: Essential Properties Of Paclitaxel Nanomedicinementioning
confidence: 99%
“…Because cancer cells spread through the lymphatic system from the site of formation, targeting the lymphatic system may aid in disease suppression. As a result, the treatment mode’s efficacy can be improved [ 39 ]. Furthermore, lipid-based nano systems help to suppress P-gp efflux transporters, which helps to reverse MDR-related issues [ 75 ].…”
Section: Colorectal Cancer: Understanding the Backgroundmentioning
confidence: 99%
“…P-gp is expressed in the epithelial cells present in the colon, kidney, adrenal pancreas, and liver, which leads to resistance to a few cytotoxic agents before the commencement of chemotherapy in the case of cancerous tissues [ 38 ]. However, in other types of tumor, there is decreased expression of P-gp during diagnosis, although it increases when the tissues are exposed to chemotherapeutic agents, which finally leads to the development of MDR in these cancerous cells [ 39 ]. Hence, there is an increase in the literature relating to the failure of a few chemotherapeutic agents when they are expressed in P-gp.…”
Section: Introductionmentioning
confidence: 99%
“…Examining the treatment and diagnosis of gastrointestinal malignancies is crucial in order to lower the incidence and mortality of the disease as well as increase patient survival rates ( 7 9 ). The use of nanotechnology in cancer research has given the scientific community optimism for the creation of revolutionary cancer therapy techniques ( 10 ). Significant efforts have been made to develop novel diagnostic and therapeutic approaches for enhancing patient quality of life and lengthening survival because gastrointestinal cancers account for more than 55% of cancer-related fatalities ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%